The Association Between Periodontitis and Cardiovascular Disease: Clinical Implications for Treatment and Prevention - Julia Krasnoborska; Katarzyna Szmyt; Sylwia Samojedny; Katarzyna Szymańska; Kamil Walczak; Klaudia Wilk-Trytko; Maciej Superson; Juia Zarębska (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose: Chronic inflammation in the oral cavity poses significant risks to both the heart and the circulatory system. A growing number of studies indicate a correlation between periodontal health and the likelihood of developing cardiovascular conditions, including myocardial infarction, coronary artery disease, hypertension, and stroke. This review aims to summarize recent reports, define current state of knowledge, and propose optimal treatment and prevention strategies. State of knowledge: Risk factors such as obesity, smoking, and genetic predisposition contribute to the development of both PD and cardiovascular diseases (CVDs). Inflammation serves as a common factor linking the two conditions, with periodontal pathogens directly affecting cardiovascular health. Epigenetic mechanisms, particularly in response to environmental stimuli, further exacerbate the relationship between PD and CVDs. Additionally, the oral microbiome plays a crucial role, with periodontal pathogens infiltrating systemic circulation and triggering immune-inflammatory responses that promote cardiovascular damage. Conclusions: People with periodontitis have a higher risk of CVDs, especially when other risk factors such as smoking and obesity are present. Periodontal treatment has been demonstrated to enhance cardiovascular health parameters. Implementing  preventive strategy, addressing both periodontitis and cardiovascular risk factors, could potentially decrease morbidity and mortality associated with cardiovascular disease.